THE INFLUENCE OF FATTY ACID SYNTHASE POLYMORPHISM ON MILK PRODUCTION TRAITS IN POLISH HOLSTEIN-FRIESIAN CATTLE - D. Ciecierska; A. Frost; W. Grzesiak; W. S. Proskura; A. Dybus; A. Olszewski (Journal of Animal and Plant Sciences, 2013)
Fatty acid synthase gene (FASN) was indicated as gene linked to milk production traits in cattle, especially milk fat yield and fatty acid composition. Fatty acid synthase coded by this gene is strictly involved in fat metabolism, so it is supposed that variability of FASN gene could influence these traits. The aim of this study was to analyze the correlation between the polymorphism of fatty acid synthase gene and milk production traits in Polish Holstein-Friesian cattle. PCR-RFLP method was used for genotyping. The major allele for analyzed locus was FASNg.17924G (f=0.63). The influence of the FASNg.17924A>G polymorphism on milk production traits was analyzed. It was found that there was a significant correlation between the FASNg.17924A>G polymorphism and selected production traits: milk yield (p≤0.05), fat yield (p≤0.05) and protein yield (p≤0.05). Further analysis of FASN gene polymorphism should be performed for the purpose of identifying of quantitative trait nucleotide (QTN) for Marker Assisted Selection.
Keywords: FASN; fatty acids; milk; polymorphism; dairy cattle